Influence of alkali metal cation on the formation of double salts in a system (MCl − Nd(Gd)Cl3 − H2O (M− Li,Na,K,Rb,Cs) at 25–100 °С - Стороженко, Д. О.; Бунякіна, Н. В.; Дрючко, О. Г.; Іваницька, І. О.; Гринчишин, Н. М. (Scientific Progress & Innovations, 2016)
We investigated phase equilibrium in aqueous systems chloride salt and alkali metal and rare earth elements (neodymium, gadolinium) at 25–100 °C by isothermal solubility in the article. Temperature and concentration limits of crystallization of initial salts and double compounds. We identified double chlorides which were synthesized and identified by physical and chemical methods of analysis.